ANALISIS KOMPARATIF KINERJA KEUANGAN PADA PT TELEKOMUNIKASI INDONESIA TBK DENGAN MENGGUNAKAN METODE ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED - Budiati, Suci Harum (Jurnal Akuntansi AKUNESA, 2014)
Financial performance is a management level gauges success in managing the financial resources of the company. Approaches use Economic Value Added (EVA) in this study were based that this approach is very good for measuring performance (management) company because the company is able to describe the efficiency of a given period. While the approach is the use of Market Value Added (MVA) based on that, MVA was able to describe how much wealth can be created by the company management to investors and companies. The use of EVA and MVA approaches in research based that this approach is very good compared with ratio analysis. This study aimed to measure the financial performance. Telkom in the period 2009-2010 by using the approach of EVA and MVA. From the results of research using the approaches of EVA and MVA found that EVA and MVA PT. Telkom positif. MVA positive value indicates that the management company is able to generate wealth for investors and companies.Keyword : Economic Value Added (EVA), Market Value Added (MVA),Financial Performance